Transplantasi Terumbu Karang Berbasis Komunitas melalui Pendidikan Fisika Kontekstual - Andi Asmar; Yuliyanti; Nurfajrin Lumalaga; Nurjannah; Inda Widiarti Hafid (Universitas Mataram, 2026)
This community service program aims to integrate contextual physics education with community-based coral reef transplantation practices. The expected implications include an increase in science literacy, technical conservation skills, and environmental care attitudes among coastal communities. The activities will be held on December 6, 2025, at Tanjung Tuwis, Banggai Regency. The service activities collaborate with Banggai Corralium as a local conservation community and involve the community and youth of Tanjung Tuwis, coastal residents, and students. The implementation method applies a participatory-educational approach that includes stages of activity design, preparation, implementation, evaluation, and follow-up. Data for the service are collected through questionnaires, observation sheets, and documentation. The results of the service show successful achievements categorized from good to very good, with transplanting technical skills at 80.42% and ecological attitudes at 81.32% for coastal communities and youth. The understanding of contextual physics is at 76.54% and the attitudes towards coastal environmental care are at 83.80% among students. Integration of academic concepts is at 82.64% and social-ecological responsibility is at 83.65% for students. Overall, the service activities effectively enhance applied competencies, ecological awareness, and cross-generational collaboration.